2023
DOI: 10.3389/fcvm.2023.1154888
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effect of probiotics or synbiotics on the risk factors in patients with coronary artery disease

Abstract: ObjectiveThe objective of this study was to study the effect of probiotics or synbiotics on the risk factors for coronary artery disease (CAD) in the context of conventional drug therapy for CAD.MethodsThe literature on probiotics or synbiotics for the treatment of CAD was collected from PubMed, Scopus, Web of Science, Embase, and Cochrane Library. The search period was conducted on November 5, 2022, and the search covered all literature before November 5, 2022. The included literature consisted of randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Two meta-analyses consisting of 16 randomized controlled trials investigating the role of several probiotics (L. acidophilus, B. bifidum, L. reuteri, L. fermentum, and L. rhamnosus) in treating coronary artery disease and lowering blood pressure, blood lipid, and blood glucose was conducted recently. These studies showed that adding probiotics to conventional medications for coronary artery disease reduced the levels of low-density lipoprotein cholesterol, fasting glucose, and hypersensitive C-reactive protein and increased the levels of highdensity lipoprotein cholesterol and nitric oxide (Lei et al, 2023;Liu L. et al, 2023). Similarly, a retrospective cohort study of 4,837 participants aged 65 years or older found that subjects who used probiotics experienced a reduced risk of all-cause mortality by nearly 41% and cardiovascular mortality by 52% (Shen et al, 2023).…”
Section: Probiotics In Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 97%
“…Two meta-analyses consisting of 16 randomized controlled trials investigating the role of several probiotics (L. acidophilus, B. bifidum, L. reuteri, L. fermentum, and L. rhamnosus) in treating coronary artery disease and lowering blood pressure, blood lipid, and blood glucose was conducted recently. These studies showed that adding probiotics to conventional medications for coronary artery disease reduced the levels of low-density lipoprotein cholesterol, fasting glucose, and hypersensitive C-reactive protein and increased the levels of highdensity lipoprotein cholesterol and nitric oxide (Lei et al, 2023;Liu L. et al, 2023). Similarly, a retrospective cohort study of 4,837 participants aged 65 years or older found that subjects who used probiotics experienced a reduced risk of all-cause mortality by nearly 41% and cardiovascular mortality by 52% (Shen et al, 2023).…”
Section: Probiotics In Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 97%
“…There is currently substantial evidence that probiotic supplementation could act as a protective agent against allergic symptoms, tumor malignancies, neurodegenerative and psychiatric diseases, cardiovascular diseases, obesity, diabetes, lactose intolerance, inflammatory bowel disease, immune system disorders, non-alcoholic fatty liver disease, diarrhea, irritable bowel syndrome, etc. [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, there is not at this time adequate conclusive evidence concerning their potential health effects, and it remains questionable whether they may be applied as supplementary treatment in any disease.…”
Section: Introductionmentioning
confidence: 99%